The F2R1 Model for Enhancing Forward Roll Learning in Eighth Grade Students - Achmat Fikri; Selvi Atesya Kesumawati; Aprizal Fikri; Dewi Septaliza; Bayu Hardiyono (UNIB Press, 2025)
The aim of this study is to develop and evaluate the effectiveness of the Fikri Forward Roll 1 (F2R1) Model in enhancing forward roll learning among eighth-grade students. This model was developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design approach. The research subjects consisted of eighth-grade students, with a small-scale trial involving 60 students from SMPN 01 Belitang and a large-scale trial involving 100 students from SMPN 02 and SMPN 03 Belitang. The product validation test was conducted by three experts: one instructional media expert, one movement learning expert, and one Physical Education, Sports, and Health (PJOK) practitioner. Data analysis employed the Content Validity Index (CVI) and Content Validity Ratio (CVR), yielding a CVI score of 3.77 and a CVR score of 0.15. These results indicate that the F2R1 Model is valid and suitable for use as a learning tool for forward rolls. Based on the findings, the F2R1 Model positively contributes to students' understanding and skills in performing forward rolls. Therefore, this model is recommended for educators to enhance movement learning at the junior high school level.